Answer:
The first number:11
The second number: 16
The third number: 64
Step-by-step explanation:
Let the first number be x
The second number be 5+x
The third number be 4(5+x)
The sum: x+5+x+4(5+x) =91
Open the brackets
x+5+x+20+4x=91
Arrange in like terms
x+x+4x+5+20=91
6x+25=91
6x=91-25
6x=66
Divde both sides by 6( the coefficient of x)
x=11
5+x=16
4(5+x) =64
6, -24, 96, -384,...
Answer:
see explanation
Step-by-step explanation:
The recursive formula allows us to calculate the next term in the sequence from the previous term.
The common ratio r = = - 4
Thus multiplying any term by - 4 gives the next term, that is
= - 4 with a₁ = 6